Registration factors that limit international mobility of people holding physiotherapy qualifications: A systematic review. Issue 6 (June 2016) - Foo, Jonathan S.; Storr, Michael; Maloney, Stephen
Highlights: Differences in education standards result in physiotherapists with varying competencies. Recognition of education may be improved through accreditation and mutual recognition. Competencies must be transitioned to different practice contexts. It is not known whether registration processes are efficient and effective. Abstract: Introduction: There is no enforced international standardisation of the physiotherapy profession. Thus, registration is used in many countries to maintain standards of care and to protect the public. However, registration may also limit international workforce mobility. Question: What is known about the professional registration factors that may limit the international mobility of people holding physiotherapy qualifications? Design: Systematic review using an electronic database search and hand searching of the World Confederation for Physical Therapy and International Network of Physiotherapy Regulatory Authorities websites. Analysis was conducted using thematic analysis. Results: 10 articles and eight websites were included from the search strategy. Data is representative of high-income English speaking countries. Four themes emerged regarding limitations to professional mobility: practice context, qualification recognition, verification of fitness to practice, and incidental limitations arising from the registration process. Conclusion: Professional mobility is limited by differences in physiotherapy education programmes, resulting in varying standards of competency. Thus, it is often necessary to verify clinical competencies through assessments, as well as determining professional attributes and ability to apply competencies in a different practice context, as part of the registration process. There has been little evaluation of registration practices, and at present, there is a need to re-evaluate current registration processes to ensure they are efficient and effective, thereby enhancing workforce mobility.